Produk Kewirausahaan dan Inovasi Lembaga Dakwah di Era Disruptif - Nur Annisa Tri Handayani; Cecep Castrawijaya (IHSANIKA : Jurnal Pendidikan Agama Islam, 2024)
The rapid development of technology and digitalization in the disruptive era has brought major changes in various sectors, including Islamic preaching. Islamic preaching institutions now have to face new challenges by innovating in their approach to preaching and developing entrepreneurial products to support their operational continuity. This article aims to explore how Islamic preaching institutions can utilize innovation and entrepreneurship to face the disruptive era. This study uses a qualitative method through literature study. Researchers use library data sources to collect data and information on the topic of entrepreneurship and Islamic preaching. The data sources collected include books, articles, and various journals related to the topic. The results of the study show that Islamic preaching institutions that are able to adapt to technological innovation and entrepreneurship have succeeded in maintaining their existence and expanding the reach of Islamic preaching.